The Impact of Systemic Insecticides: Cyantraniliprole and Flupyradifurone on the Mortality of Athalia rosae (Hymenoptera: Tenthredinidae) Based on the Biophoton-Emission of Oilseed Rape - Bálint Gerbovits; Ildikó Jócsák; Sándor Keszthelyi (Insects)
The selection of an appropriate and targeted crop protection technology for winter oilseed rape is crucial for the economic production of this crop. Insecticides belonging to the group of diamides and butenolides are available as seed treatments for winter oilseed rape and serve as effective tools for chemical crop protection. The objective of this study was to determine the multi-directional applicability of the active ingredients cyantraniliprole and flupyradifurone. Furthermore, the phenotypic detection of stress was conducted for these systemic insecticides. The results of our study show that these active ingredients acropetal and basipetal translocation are both effective against Athalia rosae (L. 1758) (Hymenoptera: Tenthredinidae). The findings from our laboratory studies indicated that the insecticidal active ingredients are effective against Athalia rosae (Hymenoptera: Tenthredinidae) via both acropetal and basipetal translocation. However, differences in the time of exertion of lethal effect were recorded. In both experimental groups, mortality was observed to reach 100% at the 96-h mark, regardless of the specific experimental conditions or the insecticide employed. An examination of the bio-photon emission of the experimental plants revealed a statistically verifiable correlation between the applied active ingredients and the photon emission intensity per unit plant surface area. The findings of our study indicate that due to their insecticidal activity, systemic insecticides also affect plant life processes by increasing photosynthetic activity per unit leaf area.